PENGADAAN TANAH UNTUK PROYEK PEMBANGUNAN MAMMINASATA DAN DAMPAKNYA DI PEDESAAN - Muhammad Ridha (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The research is aimed at answering three related questions, either directly or indirectly on the program of large-scaleland acquisition on Mamminasata Program in South Sulawesi. These questions are: 1) How does the space structure change afterMamminasata project on land acquisitions at three villages: Samata, Pacci’nongang and Romang Polong?; 2) How does the processand dynamic land acquisition at three village take place?; 3) How does the possibility of conflict take place after the project wasdone. Those questions will be answered by descriptive qualitative research method. The result shows that there was a correlationbetween large scale land acquisition on Mamminasata program with spatial change, the rise of land and extensive agrarian conflict.Keywords: development program, Mamminasata, spatial change, land acquisition.